2021
DOI: 10.3390/molecules26113478
|View full text |Cite
|
Sign up to set email alerts
|

What Can Electrochemical Methods Offer in Determining DNA–Drug Interactions?

Abstract: The interactions of compounds with DNA have been studied since the recognition of the role of nucleic acid in organisms. The design of molecules which specifically interact with DNA sequences allows for the control of the gene expression. Determining the type and strength of such interaction is an indispensable element of pharmaceutical studies. Cognition of the therapeutic action mechanisms is particularly important for designing new drugs. Owing to their sensitivity, simplicity, and low costs, electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 100 publications
(178 reference statements)
0
21
0
Order By: Relevance
“…27,45 Electrochemical investigations have shown that the signal of electrochemical oxidation varies based on the presence of guanosine (dGuo) or adenosine (dAdo) in ct-dsDNA, both before and after contact with the drug-DNA. 46,47 These signal changes are used to predict the modes of interaction that occur in DNA-drug interactions, such as intercalation, 20,21,48 electrostatic interaction, 23,49,50 groove binding, [51][52][53] etc. 54 Compared to CV, the DPV technique offers greater sensitivity and better peak resolution in examining small molecule-DNA interaction.…”
Section: Resultsmentioning
confidence: 99%
“…27,45 Electrochemical investigations have shown that the signal of electrochemical oxidation varies based on the presence of guanosine (dGuo) or adenosine (dAdo) in ct-dsDNA, both before and after contact with the drug-DNA. 46,47 These signal changes are used to predict the modes of interaction that occur in DNA-drug interactions, such as intercalation, 20,21,48 electrostatic interaction, 23,49,50 groove binding, [51][52][53] etc. 54 Compared to CV, the DPV technique offers greater sensitivity and better peak resolution in examining small molecule-DNA interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Besides chronoamperometry, staircase voltammetry (SCV) or differential pulse voltammetry (DPV) is used in electrochemical biosensors, which offer higher sensitivity, as the occurrence of capacitive charges is diminished through applying a series of regular potential pulse superimposed on the potential stair steps. , Therefore, SCV measurements were used to detect PB (0–200 μM) in human urine samples (diluted 1:3 with 5 mM PBS, pH 7.0). As shown in Figure b, a PB-dependent increase in j ox (at 0.9 V) was observed (Figure S8a), which allowed its detection in PB-spiked human urine.…”
Section: Resultsmentioning
confidence: 99%
“…SWV is commonly used for assays that determine biological binding interactions and reflect the underlying binding kinetics even with small molecules [11,12]. The sensor enabled the rapid detection of E. coli cells (less than 100 cfu) providing high sensitivity, a low LOD in a complete 3D printing device with pencil graphite used as a WE.…”
Section: Resultsmentioning
confidence: 99%